KONDISI EKONOMI SYARIAH DI INDONESIA PASCA MERGERNYA BANK SYARIAH BUMN - Angga Syahputra (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
Indonesia has the largest Muslim population in the world. With this amount, of course, it should be a capital for economic strength. However, as of November 2020, data released by the Financial Services Authority put the Islamic banking market share at 6.33%. Efforts to merge the three state-owned Sharia banks into Indonesian Sharia Banks are expected to increase the penetration of the sharia economy in Indonesia, which is still far behind when compared to conventional domestic economic movements and Islamic financial transactions in other countries. This research will describe the extent of the sharia economic conditions in Indonesia after the merger of state-owned sharia banks into BSI. This study uses a qualitative method with a type of literature review research which is obtained from various authentic sources such as books, articles, journals and trusted websites. There was a 2.7% increase in the market share of Islamic banks after the merger. This increase when compared to the existing potential and the market is still very small. However, it is hoped that this impact will continue to increase over time, especially as capital support for various financial sectors and the halal industry in the country.